The Importance of Germplasm Health in Preventing Transboundary Spread of Plant Pests and Diseases - Kumari, Safaa (Ecole Nationale Supérieure Agronomique, 2023)
This presentation will present the importance of plant pests and diseases and their impact on food security, with examples of exotic invasive plant pests and diseases that cross borders, as well as the strategic role of international Gene Banks in plant genetic resources exchange. The presentation will also emphasize how the international germplasm health units function, what they are, and the measures and procedures followed to achieve safe movement of genetic resources. The fact that seeds/germplasm are an important pathway for the spread of pests and plant diseases through human activities, germplasm collection and distribution, will be emphasized. The presentation will also bring up the fact that pests have increased significantly in recent years, through global trade of agricultural products and climate change. Finally, the most important required steps to preserve global food systems, such as sound planning, rapid action, development of crops resistant to diseases and insect pests, and safe exchange of germplasm to prevent the international spread of plant pests and diseases, will be discussed.